Ionosphere Monitoring with Remote Sensing - Fabio Giannattasio (Remote Sensing, 2022)
Characterising the physical properties of the Earth’s ionosphere is fundamental to shed light on the dynamic processes occurring therein on a wide range of both spatial and temporal scales and to understand several phenomena relevant to Space Weather [...]